Income and tax burden of the middle class in Europe - Mathias Dolls; Florian Dorn; David Gstrein; Max Lay (EconPol Forum, 2023)
Middle class incomes in the EU are highest in Luxembourg, Denmark, Finland, Austria, and Sweden, and lowest in Eastern European countries. The middle class in Bulgaria and Romania are at the bottom of EU nominal incomes, but their living costs are just half of the EU average. When accounting for differences in purchasing power in the EU, the middle class in Luxembourg, Austria, Germany, and Finland can buy the most with their income. The purchasing power of the middle class in Eastern Europe is the lowest, but inequality in incomes of the middle class in different EU member states is less pronounced when cost of living is considered. The tax burden of the EU middle classes differs depending on the household's country of residence. The effective tax rates follow a progression in all countries. Lower-middle incomes are taxed less, while upper-middle ones are taxed the most. Families are generally less burdened by the tax and transfer system than singles with the same gross incomes. However, countries differ in whether families with single-earner households are more likely to enjoy tax advantages, or families with equal earners. In general, the middle class in Denmark, Belgium, Germany, Finland, Lithuania, Slovenia, and the Netherlands is taxed the most. Among others, France, Poland, Italy, Luxembourg, Sweden, and Austria, impose average tax burdens on their middle classes. The middle classes in Spain, Greece, Estonia, Portugal, Cyprus, Bulgaria, and Romania all rank below the average tax burden in the EU
Keywords: 330